Hernia diafragmática traumática en pediatría (2011)
Traumatic diaphragmatic hernia in pediatricsTrauma isn't often a condition seen in children, especially those ones with an important severity related to acts of interpersonalviolence by individuals of the same age. There are few records and casuistic in this regard, not only about these acts, but alsoabout the condition to describe and the main focus of this writing. Traumatic diaphragmatic hernia is a particular conditionof a population with high exposure to risky activities in an age group that includes the adult and young adult population. Inthis article, a case example of this particular condition is presented, with relevant details about its evolution and outcome. Keywords. Traumatic diaphragmatic hernia. Wounds and injuries. Multiple trauma. Pediatrics. Violence.v